2012
DOI: 10.1172/jci64896
|View full text |Cite
|
Sign up to set email alerts
|

IL-13–induced airway mucus production is attenuated by MAPK13 inhibition

Abstract: Increased mucus production is a common cause of morbidity and mortality in inflammatory airway diseases, including asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis. However, the precise molecular mechanisms for pathogenic mucus production are largely undetermined. Accordingly, there are no specific and effective anti-mucus therapeutics. Here, we define a signaling pathway from chloride channel calcium-activated 1 (CLCA1) to MAPK13 that is responsible for IL-13-driven mucus production i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
265
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(288 citation statements)
references
References 71 publications
23
265
0
Order By: Relevance
“…2010; Alevy et al. 2012). Goblet cell metaplasia is increased in smokers, and several studies using cigarette smoke have shown the induction of MUC5AC (Wright et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Alevy et al. 2012). Goblet cell metaplasia is increased in smokers, and several studies using cigarette smoke have shown the induction of MUC5AC (Wright et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, airway progenitor cells differentiate into functional ciliated and secretory cells when subjected to an ALI (air-liquid interface) condition for 18-21 d. The best, established model for induction of goblet cells is treatment with IL13. 11,37 We devised a protocol whereby treatment of cells with IL13 for 7 or 21 d ( Fig. 2A) resulted in an increased number of MUC5AC-positive cells and elevated levels of MUC5AC RNA (Fig.…”
Section: Il13 Induces Muc5ac Secretion In Human Tracheobronchial Epitmentioning
confidence: 99%
“…Using approaches similar to these, our group has recently demonstrated that airway epithelial cell IL33 (interleukin 33) leads to IL13 production and lung pathology in a mouse model and in cells obtained from patients with COPD. [11][12][13][14] IL13 is a Th2-type cytokine that is elevated in COPD as well as in asthma and other lung diseases. 11,[15][16][17] In the airway, IL13 regulates the differentiation of epithelial cells to goblet cells via intracellular signaling through the IL4R (interleukin 4 receptor) and IL13RA1 (interleukin 13 receptor, a 1) receptor heterodimer and STAT6 (signal transducer and activator of transcription 6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations